Bank Risk-Taking and the Real Economy: Evidence from the Housing Boom and Its Aftermath - Falato, Antonio; Favara, Giovanni; Scharfstein, David (Review of Financial Studies, 2026)
During the U.S. housing credit boom, publicly traded banks increased mortgage lending activity and relaxed standards much more than privately held banks. The increase in risk had real effects for a variety of county-level aggregates including employment and consumption. Cross-sectional evidence and a quasi-experiment indicate that the increase in risk stemmed from the institutional ownership and the equity compensation of publicly traded banks, in turn leading banks to place greater weight on short-term equity performance. These results are consistent with the view that a focus on short-term earnings and stock prices amplifies boom–bust credit cycles, in turn leading to real cycles for the aggregate economy.